A Real-Business-Cycle model with endogenous discounting and a government sector - Aleksandar Vasilev (Notas Economicas, 2021)
This paper takes an otherwise standard real-business-cycle (RBC) setup with government sector, and augments it with an output-expropriation mechanism and shocks to institutional quality in order to study business cycle fluctuations. The extraction decision is endogenous: households can use their time either productively, or engage in opportunistic activities. Stronger institutions decrease the size of the available resources for capture, and suppress corrupt behavior. As a test case, the model is calibrated to Bulgaria after the introduction of the currency board (1999-2018). Overall, the shocks to institutional quality generate business cycles of the same magnitude as in data, which suggests that political economy factors might be the major driving force behind the observed economic fluctuations in Bulgaria. Another interesting result, generated by the model, is that on average, the estimated size of eWe introduce an endogenous discount factor as in Uzawa (1968) and Schmitt-Grohe and Uribe (2003) into a real-business-cycle setup with government sector and Greenwood et al. (1988) preferences. We calibrate the artificial economy to Bulgarian data for the period following the introduction of the currency board arrangement (1999-2018). We investigate the quantitative importance of endogenous discounting for the propagation of cyclical fluctuations in Bulgaria. The presence of an endogenous discount factor improves the model performance against data, and in addition this extended setup performs better than the standard RBC model framework with a constant discount factor, e.g., Vasilev (2009).vaded resources is approximately one-fourth of output, which is very close to the estimates of the unofficial economy share, e.g., European Commission (2014) and Medina and Schneider (2017).
Keywords: E32; E24; 330; Business Cycles; Uzawa preferences; Endogenous Discounting; Bulgaria